Production and Income Over Feed and Chick Cost (IOFCC) of Broiler Chicken Which Feed The Fermented Dragon Fruit Skin Ration (Hylocereus Polyrhizus) - I N. Tirta Ariana; Gusti A. M. Kristina Dewi; M. Wirapartha; I. W. Wijana; I. K. Anom Wiyana; N. W. Sitiari (Jurnal Ekonomi dan Bisnis Jagaditha, 2018)
Abstract-The objective of the study is to know the production and the income over feed and chick cost (IOFCC) of broiler chicken which feed the fermented dragon fruit skin ration (Hylocereus Polyrhizus). The design of the study was Randomized Complete Design (RCD) with 3 treatments and 5 replications, where each replication consisted of 10 DOC broiler chicken; so total chicken used was 150 heads. Treatments given were: R0: ration of fruitless fruit skin of dragon, fermented; R1: ration with 5% flour of fermented dragon fruit skin and R2: ration with 7% fermented dragon fruit skin flour. Variables observed: final body weight, body weight gain, ration consumption, FCR, Income over Feed and Chick Cost (IOFCC). The data obtained were analyzed by variance, if between the treatments were significantly different (P